The Effect of Using the Tiktok Application as a Learning Media on the Activeness and Learning Outcomes of Class XI Social Sciences Students in Sociology Subjects at SMA N 1 Ampek Angkek - Ardiana, Elsa; Ananda, Azwar (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This research is motivated by education which is a process of changing attitudes in a person and knowledge in its implementation requires careful planning in order to achieve educational goals. The use and selection of learning media is one way to improve learning. Tiktok as a video entertainment application has many features that allow it to be used as an audiovisual learning medium. This study aims to determine how the effect of using the Tiktok application as a learning media on the activity and learning outcomes of students in the Sociology Subjects of class XI Social Sciences at SMA N 1 Ampek Angkek.The research approach uses a Quasi-Experimental quantitative approach using a 2x2 Factorial research design. The research location is SMA N 1 Ampek Angkek which is located in Kanagarian Lambah, Ampek Angkek District, Agam Regency. The population in this study were students of class XI IPS and the sample of this study were students of class XI IPS 4 for the Experiment class who would use the Tiktok application as a learning medium and XI IPS 1 for the control class who did not use the Tiktok application as a learning medium. Data analysis used quantitative analysis techniques using t-test to test the hypothesis. The results of the study found that: 1). There are differences in the activity of students who use Tiktok as a learning medium with students who do not use the Tiktok application as a learning medium, 2). There are differences in the learning outcomes of students who use the Tiktok application as a learning medium with students who do not use the Tiktok application as a learning medium. This happens because the Tiktok application can stimulate the active learning of students through activities that are not boring. By looking at the learning video content before students enter the learning material, it stimulates students to show an attitude of interest in learning so that these students are involved in every learning process and students can produce good learning outcomes.